Symptom experiences of patients after cardiac valve surgery: A qualitative study - Jiajia Ban; Yuexiu Hu; Hong Huang; Ping Zhang; Shan Dong; Yujie Zhou; Ling Yuan; Yunyan Su (PLoS ONE, 2026)
Introduction Heart valve disease is a leading cause of morbidity and mortality worldwide, with surgery being the gold standard treatment.Although clinical management focuses on postoperative functional recovery, the burden of symptoms is often inadequately characterized, despite its significant impact on healthcare resource utilization and health-related quality of life.Current evidence highlights notable gaps in understanding the subjective symptom experience after cardiac valve surgery, particularly regarding the long-term evolution of symptoms and their psychosocial impact. Objective This qualitative study aimed to systematically identify and characterize the most troubling symptom domains, specific symptoms, and symptom coping styles in patients after aortic or mitral valve replacement. Methods We conducted semi-structured interviews with 14 adult patients (ages 26-76 years) who underwent minimally invasive or sternotomy-based valve replacement surgery at a tertiary cardiovascular center in Nanjing, China. Results Fourteen patients (ages 26–76 years) participated in the study, from whose narratives three overarching themes and 14 subthemes were derived through thematic analysis.The analysis revealed the following:1) Physical Dimension of Symptom Experience, covering dynamic multisystem symptoms like respiratory discomfort, pharyngeal/oral issues, circulatory problems, digestive/excretory troubles, surgical pain, fatigue/weakness, and sleep disturbance; 2) Psychological Dimension of Symptom Experience, including intrinsic psychological adaptation (positive/negative) and emotional reactions to external factors (clinician interactions, family support, medical technology dependence); 3) Cognitive Dimension of Symptom Experience, involving transient ICU cognitive changes (disorientation, hallucinations) and symptom cognition (viewing pain/fatigue as inevitable, age-symptom speculation); 4) Symptom Experience and Coping Strategies in the Behavioral Dimension, encompassing passive symptom-induced behaviors and active coping (non-pharmacological, pharmacological, support-seeking). Conclusions This study shows cardiac valve surgery patients have multidimensional, dynamic postoperative experiences. They face diverse multisystem physical symptoms, mixed positive/negative psychological states, transient ICU-related cognitive changes, and both passive and active coping strategies (with individual differences). It highlights the need for holistic, individualized postoperative care to improve recovery and quality of life.